PENDAMPINGAN PENYUSUNAN DETAIL ENGINERING DESAIN (DED) PENATAAN KAWASAN PERMUKIMAN DI KECAMATAN TANJUNG - Pratama, Indah Arry; Desimal, Iwan; Muhsinun, Muhsinun (LPPM Institut Pendidikan Nusantara Global, 2022)
Based on Undang-undang no 1 Tahun 2011, The implementation of residential areas is carried out with the aim of realizing an area that functions as a residential environment and a place for activities that support a planned, comprehensive, integrated, and sustainable life and livelihood in accordance with the spatial plan. The purpose of this assistance in the preparation of Detail Engineering Design (DED) is to realize a plan that is in accordance with the required technical standards. This service activity begins with an understanding of the Slum issued by the Mayor of Kota Bima, then proceeds with conducting a site survey to see existing problems, and finally by carrying out Focus Group Discussions (FGD) and technical meetings offline and online. This Community activity produces a Detailed Engineering Design (DED) and a profile of the Sapaga residential area arrangement in Kota Bima which is the basis for planning regional planning in the area. In the preparation of Detail Engineering Design activities, the expected output includes 7 (seven) parameters for structuring slum areas, only during implementation activities, of course, there are still some adjustments related to field conditions.